SAID NURSI EDUCATION CONCEPT: INTEGRATION OF SPIRITUAL, INTELLECTUAL, AND MORAL DIMENSIONS - Nur Hadi Ihsan; Hasanah Purnamasari; Dhita Ayomi Purwaningtyas (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
Recently, many people have made Western education a model for the advancement of civilization. Western curriculum education is, therefore, offered as an alternative system. In the case of Turkey, this adoption of the idea produced the gap between traditional madrasa graduates and the graduate of the secular school, which impacts the emergence of a crisis of civilization. This article tries to offer a solution to this crisis by bringing up the idea of a contemporary Turkish thinker, Said Nursi, in his concept of reformed Islamic education. This concept has three essential elements of education: spiritual, intellectual, and moral, realized by Said Nursi through Medresetuz Zahra. Nursi expresses the integration of these three aspects in his masterpiece, Resale-I Nur. This is qualitative library research using documentary techniques to collect the data. The collected data are analyzed utilizing the descriptive-analytical method.